Direct health costs of malaria in the Regional Military Hospital of Uíge, Angola - Ariana Fernández García; Manuel Collazo Herrera; Nzuzi Pedro Mendes; Justino Pinto Hossi (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: In Angola malaria is still the first cause of death. This disease has a negative impact on the population's health and the social development of this country. In addition it influences directly  its level of poverty. Objective: to calculate the sanitary direct cost of malaria patient's caring in a hospital in Angola. Method: a descriptive study, specifically a partial economical evaluation, called cost description. The period covered four months (January-april 2014). A number of 63 patients were included, assisted at the Military Hospital of Uíge, Republic of Angola. The disease cost methodological approach was applied from the health institutional perspective, the modeled micro-funding"bottom-up" and the Methodological Guide for Health Economical Evaluations in Cuba. Results: the total cost of assisting a malaria patient for the institution was 2 752 536.24 kwanzas (28 114.93 dollars). The complicated malaria cost was higher (2 125 718.66 kwanzas) with respects to simple malaria (626 269.59 kwanzas), while assisting one patient was 8 450.74 kwanzas. Conclusion: treatment to complicated malaria represents  higher expenses for the hospital which tripled the cost of simple malaria.